PHOTOCATALYTIC DEGRADATION OF PENTACHLOROPHENOL (PCP) USING IMOBILIZED TiO2 - Winarti Andayani; Agustin Sumartono (Universitas Gadjah Mada, 2007)
Imobilization of titanium plate using titanium diisopropoxide as a precursor, that will be used as a catalyst for degradation of pentachlorophenol (PCP) has been done. In this study 10 ppm of pentachlorophenol (PCP) solution at pH 5 was used as a model of organic polutant. Irradiation was done with and without TiO2 as a catalyst. Sampling was done at interval time of 15, 30, 45, 60, 75, 90, 105, 120, 135, 150, 165, 180, 195, 210, 225 and 240 minutes. Parameter examined after irradiation were the changes of spectrum and pH, the formation of chloride ions and intermediate compounds. The decreased of pH and PCP concentration and the formation of chloride ions and intermediate compounds showed that PCP has already degraded.